OPTIMASI KINERJA TURBIN PELTON DENGAN MENGGUNAKAN2 NOZZLE DAN KEMIRINGAN BUCKET -8° DAN 8°: Array - Simbolon, Jodi; Junaidi, Junaidi; Kurniawan, Fadly Ahmad (JiTEKH, 2020)
The power generated in the water turbine (Pelton turbine) varies depending on the flow of water entering the turbine. The research was conducted in the mechanical engineering laboratory of the Faculty of Mechanical Engineering, Universitas Harapan Medan. The experimental method is the method used in this study. By varying the 2 nozzles, the flow of water (Q) at 300 m3 / s and 375m3 / s, and at a bucket slope of -8o and 8o.The results obtained are: At -8o bucket slope the maximum turbine output power produced is 340 watts, and the minimum turbine output power is 250 watts. In the 8o tilt bucket, the maximum turbine output power generated is 460 watts, and the minimum turbine output power is 340 watts. The greatest efficiency is found in the maximum power of the turbine, which is 460 watts with an efficiency of 16%, which is found in the 8o tilt bucket.